Varying structural motifs in the salen based metal complexes of Co(ii), Ni(ii) and Cu(ii): synthesis, crystal structures, molecular dynamics and biological activities. Issue 47 (21st November 2016) - Saini, Anoop Kumar; Kumari, Pratibha; Sharma, Vinay; Mathur, Pradeep; Mobin, Shaikh M.
Abstract : Four new metal complexes which demonstrates varying structural motifs from monomeric to dimeric to tetrameric complexes by slightly altering the reaction conditions and their biological applications. Abstract : Herein, we report the structural and biological activities of a deprotonated Schiff base ligand (H2 L) H2 L = 1, 1′-(1 E, 1′ E )-(2, 4, 6-trimethyl-1, 3-phenylene)bis(azan-1-yl-1-ylidene)bis(methan-1-yl-1-ylidene)dinaphthalen-2-ol towards Co(ii ), Ni(ii ) and Cu(ii ) complexes obtained under different conditions. Four new metal complexes have been synthesized: isostructural dimers [Co(L)]2 (1 )/[Cu(L)]2 (3 ), a monomer (Cl3 NiH2 L)·(Et3 NH) (2 ) and a tetramer [Cu(L)]4 (4 ). The bioactivity of1–3 has been investigated through molecular docking with DNA and various proteins, known to be involved in the proliferation of viral diseases or progression of cancer. Complex1 shows the best results, through a strong binding affinity with NS2B/NS3 protease (dengue virus) in terms of binding energy (−11.21 kcal mol −1 ) and inhibition constant (6.02 nM). The experimental evidence for the effective binding of1–4 with the Bovine Serum Albumin (BSA) protein and calf thymus DNA (CT-DNA) is in agreement with our molecular docking results. In addition, the cytotoxicity and antibacterial activity of1–4 were examined and found to be compatible with biological systems, with4 showing the highest antibacterial activity. All four complexes were analyzed by elemental analysis and UV/vis analysis, and their molecular structures were authenticated by single crystal X-ray studies.